OPTICAL PROPERTIES AND CHEMICAL CHARACTERIZATION OF WOODY SYRUP BY USING METHODS OF APPLIED PHOTONICS - Poli Radusheva; Krastena Nikolova; Nadezhda Petkova; Radoslava Gabrova; Darina Naydenova (Peytchinski Publishing, 2018)
Introduction: The natural woody syrup is a typical product from the Canary Islands and America. It is often used for health food supplement for children, athletes and elderly because it has well-pronounced antioxidant properties. The interest in this syrup is increasing because it is often used in homeopathic medicine and consists of phenolic content. Antioxidants reduce cell damaging effects of free radicals. They are more effective in vitro antioxidants than vitamins D and C and have a significant effect towards protection of unwanted in vivo oxidation of proteins and lipids. Objective: The natural woody syrup is prepared from Canadian maple syrup and syrup from 5 types of palms from Southeast Asia. The nutritional properties (such as the content of sugars) were analyzed. The antioxidant activity, total phenolic content and optical properties have been investigated. Purpose: The aim of this study is to explore the relations between fluorescence in natural woody syrup and its total phenolic content and total antioxidant activity in view of the usefulness of this product for human health and to determine their nutrient composition by the physico-chemical properties. Materials and methods: The natural woody syrup will be investigated by using methods of applied photonic, 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and Ferric reducing antioxidant power (FRAP) methods for antioxidant activity, Folin-Ciocalteu reagent for total phenols and High-Performance Liquid Chromatography Refractive Index Detector HPLC-RID analysis for determination of the sugar content. Results: The dependence between antioxidant activity and total phenolic content was established. The sample has a small quantity of flavonoids, and for this reason, there is not the distinct peak at 380 nm. Excitation in the visible region is suitable for distinguishing the riboflavin and pigments. Conclusions: The fluorescence of the syrup was correlated with their antioxidant activity. Two emission fluorescence maxima have been observed: -The first one is attributed to the riboflavin in the region 550 nm - 580 nm -The second one is connected with the pigments similar to the chlorophyll at about 690 nm.